2020
DOI: 10.3390/agronomy10010146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Fall Dormancy-Rating Alfalfa Cultivars for Forage Yield in a Semiarid Environment

Abstract: Alfalfa is one of the most important, nutritive, and high yielding forage legumes planted across the US. Fall dormancy in alfalfa influences forage yield characteristics and the plants persistence mostly under the cold and temperate climate. The objective of this study was to evaluate alfalfa cultivars with different fall dormancy-ratings for their forage yield at each cut and the annual forage yield. Two sets of 24 alfalfa cultivars were evaluated in a field experiment conducted at the Agricultural Science Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
4
20
0
Order By: Relevance
“…The similar results were also obtained from another study [45]. The results of the fall dormancy ratings of the alfalfa cultivars were consistent with several previous studies [22,46,47]. rate, indicating that no effects of fall dormancy levels were observed on the forage yield in this study.…”
Section: Major Factors Influencing Production Adaptability Of Alfalfasupporting
confidence: 93%
See 2 more Smart Citations
“…The similar results were also obtained from another study [45]. The results of the fall dormancy ratings of the alfalfa cultivars were consistent with several previous studies [22,46,47]. rate, indicating that no effects of fall dormancy levels were observed on the forage yield in this study.…”
Section: Major Factors Influencing Production Adaptability Of Alfalfasupporting
confidence: 93%
“…The similar results were also obtained from another study [45]. The results of the fall dormancy ratings of the alfalfa cultivars were consistent with several previous studies [22,46,47].…”
Section: Major Factors Influencing Production Adaptability Of Alfalfasupporting
confidence: 92%
See 1 more Smart Citation
“…There are fewer reports on the use of the ASI in alfalfa [12,19] compared to crop production [24][25][26][27]31]. ASI reflects the overall growth status of alfalfa after wintering.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of alfalfa, forage kochia (Bassia prostrata), and Napier grass (Cenchrus purpureus) further demonstrated the effects of genotype × environment interaction for rangeland agriculture. Evaluation of the effect of alfalfa fall dormancy on forage yield in the USA southern Great Plains found that less dormant materials possessed higher yields, but that there were interactions between forage harvest and dormancy class [16]. Forage kochia is valued as a rangeland plant material for its drought and salinity tolerance, competitiveness with annual weedy species, and for its nutritional value.…”
mentioning
confidence: 99%